Diagnostic Value of Imaging Combined With Tumor Markers in Early Detection of Lung Cancer - Wei, Su-Ju; Wang, Li-Ping; Wang, Jun-Yan; Ma, Jing-Xu; Chuan, Feng-Bin; Zhang, Yu-Dong (Frontiers in Surgery, 2021)
Objective: To explore the diagnostic value of imaging plus tumor markers in early detection of lung cancer. Methods: Sixty lung cancer patients up in our hospital from January 2018 to January 2019 were selected as group A. They were matched with 60 benign lung disease patients as group B and 60 healthy subjects examined in our hospital as group C. We assessed carcino-embryonic antigen (CEA), CYFRA21-1, and neuron-specific enolase (NSE) and explore the diagnostic value of tumor markers plus imaging in lung cancer diagnosis. Results: The CEA, CYFRA21-1, and NSE in group A were highly superior to group B and group C, those in group B were highly superior to group C (all P<0.001). CEA had the highest sensitivity (56.7%), and NSE had the highest specificity (93.3%). The tumor markers plus imaging had the highest sensitivity of different types of lung cancer, and the sensitivity to lung cancer (90.0%) was superior to other diagnostic methods (P<0.05). Conclusion: The tumor markers plus imaging is of great significance in early lung cancer diagnosis and has a high reference value in judging the pathological classification.